2018
DOI: 10.1111/voxs.12434
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and risk perception surrounding blood transfusion in Trinidad and Tobago

Abstract: Background and objectives Trinidad and Tobago is a developing country with a hospital‐based, replacement blood donation system, low annual donation rate and high frequency of donor transfusion transmissible infections. Previous studies suggest a need for more information to improve total donations and encourage conversion to voluntary non‐remunerated blood donation. The aim of this study was to investigate public knowledge and perceptions about receiving blood to derive information for designing a safe blood d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…In developed countries with VNRD‐based systems, high risk perception is associated with female gender, lower education, married status and no history of blood donation or receipt 16 . Similar studies in FRD‐based systems are rarer but risk perception was higher among older males in Saudi Arabia 37 and among young females in TTO 28 . The latter finding in TTO has been reinforced in this survey.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In developed countries with VNRD‐based systems, high risk perception is associated with female gender, lower education, married status and no history of blood donation or receipt 16 . Similar studies in FRD‐based systems are rarer but risk perception was higher among older males in Saudi Arabia 37 and among young females in TTO 28 . The latter finding in TTO has been reinforced in this survey.…”
Section: Discussionsupporting
confidence: 74%
“…Another KAP study showed high risk perception regarding transfusion receipt that affected willingness to both donate and accept blood. The authors recommended inclusion of blood transfusion information in campaigns to promote voluntary nonremunerated blood donation 28 . The present study was conducted to reassess blood donation and transfusion knowledge, attitudes, and risk perception in TTO and investigate them in BAH for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Each credit could be converted to a 'chit' in the name of a patient of the donor's choice. An attempt to convert existing donors to VNRD failed in 2011 [12][13][14]. Although prohibited by law, the practice of secretly paying professional donors to pose as FRDs is long-standing and has become a subjective norm [15].…”
Section: Introductionmentioning
confidence: 99%